MENURUNKAN LEAD TIME PROSES MELEPAS SENSOR SWITCH MUNDUR PADA UNIT ISUZU GIGA DENGAN MEMBUAT SST SWITCH REVERSE TRACKER DI PT ASTRA INTERNATIONAL TBK - ISUZU SALES OPERATION CABANG KARAWANG - Nugraha, Afitro Adam; Widyartono, Andreas Edi; Purwoko, Yohanes Pembabtis Agung; Sutama, Yohanes Climacus; Maghetan, Yogas Weka (Universitas Muhammadiyah Metro, 2024)
AbstractAstra Isuzu Sales Operations Karawang branch is the official workshop of the Isuzu brand which is a PT network company. Astra International – Isuzu Sales Operations (ISO) which provides Analysis, Overhoul, Adjusting, Replacing, Retrofit, Periodic Service, Maintenance and so on. Lead time is an important factor to measure how long the work process takes to determine quality, of course, in an industry, time is money, the longer the work takes, the more time it will hamper other work. The problem that the author found was that it was difficult to remove the reverse switch sensor on the Isuzu Giga unit because its location was very difficult to reach using tools and very limited space. So far, technicians have used the Fukung 24 tool to remove it, but it took quite a long time, namely around 35 minutes, from As a result of the analysis carried out, the root of the problem can be identified, and to overcome this the author created the SST Switch Reverse Tracker Sensor to simplify and speed up the work with the processing time using the SST Switch Reverse Tracker Sensor being 8 minutes, making the work more effective and efficient so that the productivity of technicians and Workshop stalls are maximized and wasted time is lost.ektif dan Efisien, Sensor Switch Mundur, SST